The 16th International and Iranian Congress of Microbiology" Tehran, Iran. 25-27 Aug 2015 - Proceeding Microbiology (Tehran University of Medical Sciences, 2016)
The 16th International and Iranian Congress of Microbiology" Tehran, Iran. 25-27 Aug 2015